2018
DOI: 10.1016/j.ctro.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

SYSTEMS-2: A randomised phase II study of radiotherapy dose escalation for pain control in malignant pleural mesothelioma

Abstract: HighlightsA randomised phase II trial of radiotherapy dose escalation for pain control in MPM.Comparison of 2 hypofractionated regimes (20 Gy/5# and 36 Gy/6#).Highly conformal radiotherapy techniques used to aid safe dose escalation.Primary outcome: pain control at week 5 at radiotherapy site.Recruitment target: 112 patients from 10 to 15 UK centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…In initial experiences, intensity modulated proton therapy (IMPT) has shown feasibility and lower mean doses to the contralateral lung, heart, esophagus, liver, and ipsilateral kidney compared with IMRT [ 17 , 28 , 29 , 30 ]. Dose escalation has not been shown to significantly reduce local failure after EPP [ 15 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In initial experiences, intensity modulated proton therapy (IMPT) has shown feasibility and lower mean doses to the contralateral lung, heart, esophagus, liver, and ipsilateral kidney compared with IMRT [ 17 , 28 , 29 , 30 ]. Dose escalation has not been shown to significantly reduce local failure after EPP [ 15 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The encouraging results of SYSTEMS-1 led the researchers to design a second trial, SYSTEMS-2[ 81 ], to compare the effects of an escalated dose (36 Gy in six fractions for 2 wk) and a standard dose (20 Gy in five fractions for 1 wk) delivered only to the tumor responsible for the pain (hemithoracic radiation was not contemplated). The planned sample size is 112 patients and patients will be treated with IMRT or, where not available, three-dimensional (3D) radiotherapy.…”
Section: Clinical Indications By Tumor Stage and Treatmentmentioning
confidence: 99%
“…95 The authors concluded that RT for pain control in MPM is effective in some patients and plan to follow up their study with SYSTEMS-2, which will compare standard palliative RT dosing at 20 Gy in five daily fractions to an escalated dosing of 36 Gy in six daily fractions. 96…”
Section: Radiation Therapymentioning
confidence: 99%